2001
DOI: 10.1063/1.1345852
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in microcrystalline-transition state: Origin of Si-nucleation and microcrystallization at higher rf power from Ar-diluted SiH4 plasma

Abstract: Using very high Ar-dilution to the SiH4 plasma, good quality amorphous Si:H films could be obtained at very low rf power. The a-Si:H film, prepared at a very low deposition rate of ∼10 Å/min, exhibited a σPh∼1×10−4 S cm−1, σPh/σD∼105, a notably wide optical gap of 2.10 eV and a very good stability against thermal annealing effects with reasonable light induced degradation. At higher rf power undoped μc-Si:H films were prepared with a high σD∼1×10−4 S cm−1, at a deposition rate of 30 Å/min from <1 sccm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…As R is increased (SiH 4 flow rate is decreased) further, the deposition rate decreases drastically (1.3 A/s, for R = 630), resulting in a very low thickness of the film. Even for this argon dilution, the deposition rate is found to be much higher compared to that reported in the literature (0.5-0.83Å/s) [5]. For R ≤ 400 the band gap is estimated to be ∼1.85-1.90 eV, which increases to 2.16 eV for R = 630.…”
Section: Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…As R is increased (SiH 4 flow rate is decreased) further, the deposition rate decreases drastically (1.3 A/s, for R = 630), resulting in a very low thickness of the film. Even for this argon dilution, the deposition rate is found to be much higher compared to that reported in the literature (0.5-0.83Å/s) [5]. For R ≤ 400 the band gap is estimated to be ∼1.85-1.90 eV, which increases to 2.16 eV for R = 630.…”
Section: Resultsmentioning
confidence: 44%
“…In the case of argon dilution other radicals like Si, SiH, SiH 2 are present in the plasma. Due to their low mobility and high reactivity these species react with Si-H bond on the surface resulting in columnar growth with high deposition rate [4,5,11]. In our case, when both hydrogen and argon are used as diluents, the presence of atomic hydrogen and Ar * causes effective dissociation of SiH 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average film deposition rate (R D ) as measured by Dektak 6M surface profiler, has been given in table 1. It has been observed that the film deposition rate follows a sublinear dependence with P, hence produces the SiH 4 depleted plasma which could initiate heterogeneity and promote nanocrystallization in the network (Knights 1980;Matsuda 1983;Das et al 2001).…”
Section: Resultsmentioning
confidence: 98%
“…He, Ar, Xe) dilution to SiH 4 is one way of producing high density plasma at low electrical excitation to increase the deposition rate. However, high Ar dilution leads to columnar growth and mostly produce defective network (Knights 1980;Das et al 2001), while Xe dilution maintains an amorphous nature of the network even at a very high RF power applied to the plasma (Matsuda et al 1991). He dilution undoubtedly increases the growth rate, however, it has not been reported to produce nanocrystalline silicon network (Tchakarov et al 2004).…”
Section: Introductionmentioning
confidence: 94%